Systematic Literatur Review: Bidang Penerapan Budaya Digital melalui Implementasinya - Tegas Hadiyanto; Jhon Veri (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Industrial revolution 4.0 is a continuation of the industrial development process that is taking place. Progress in this era is marked by the integration of Cyber ​​Physical Systems (CFS), industrial wireless networks, and other supporting technologies. Utilization of artificial intelligence, robotics and the Internet of Things (IoT) to create interconnected intelligent systems. With the existence of intelligent systems and smart machines that are connected to each other, automation, blood exchange in the production process, combining physical connection networks with cloud computing through increasingly sophisticated internet connectivity has implications for people's daily lives. Advances in information technology have brought many changes to society's daily life. The use of information technology has become a digital culture in today's society. The aim of this research is to answer the research question, namely to find out the application of digital culture in several fields including organizations, the social sector and the educational sector. And how to implement digital culture in this field, whether using applications, social media and information technology devices. This research method uses a Systematic Literature Review, by looking for journal articles and proceedings published between 2020 and 2024. The mapping results show that digital culture is widely applied in the organizational, social and educational fields by implementing applications, social media and technological devices. information.